Analysis the Impact of Covid-19 Pandemic on Hotel and Restaurant Tax Revenues in Badung Regency - Ni Putu Lia Kisnayanti; I Wayan Karmana; I Gede Made Karma (JURNAL PAJAK INDONESIA, 2021)
Badung Regency is one of the areas that has very developed tourism potential with Hotel and Restaurant Tax (PHR) revenues. Since the Covid-19 pandemic, the tourism sector in Badung Regency stopped operating, so that the regional government issued a policy such as rationalizing the target of PHR revenues. In addition, the realization of PHR revenues in 2020 has decreased when compared to the realization of PHR revenues in the previous period. This study discusses PHR revenues before and during the Covid-19 pandemic. The purpose of this study was to determine an impact of the Covid-19 pandemic on PHR revenues in Badung Regency. The data analysis technique in this research is quantitative with the type of comparative analysis. In testing hypotheses, the program used is SPSS version 23. Hypothesis testing of PHR revenues was tested using the Paired Sample t-Test method. The results of testing the Hotel and Restaurant Tax revenue hypothesis show that there is a difference between Hotel and Restaurant Tax revenue before and during the Covid-19 pandemic. The difference between Hotel and Restaurant Tax revenues before and during the Covid-19 pandemic shows that the Covid-19 pandemic has an impact on Hotel Tax revenue in Badung Regency